Unusual oral manifestation of Kindler syndrome: a case report and review of literature - Bhandary, Rahul; Venugopalan, Geethu; Hegde, Padmaraj (Frontiers in Oral Health, 2024)
Kindler syndrome (KS) is a rare autosomal recessive genodermatosis characterized by congenital acral blistering, that typically presents in infancy and is followed by the development of characteristic poikilodermatous pigmentation and photosensitivity in later life. These clinical manifestations arise from mutations in the FERMT-1 (Fermitin family homologue 1) that encodes kindlin-1, a protein localized to focal adhesions in keratinocytes. Kindlin-1 plays a crucial role in integrin receptor activation, which is essential for cell adhesion and migration. Most KS cases exhibit reduced or absent kindlin-1 expression, leading to defective integrin activation and impaired cell adhesion and migration processes. This impaired cell adhesion ultimately results in the blistering phenotype observed in KS. Oral manifestations of KS are frequently under-reported and misdiagnosed, potentially leading to delayed or incorrect treatment. Furthermore, diabetes mellitus (DM) can further exacerbate the severity of KS due to impaired epidermal barrier function and compromised periodontal health. This co-morbidity creates a synergistic effect. Periodontal infection, often exacerbated by DM through a caspase-3-dependent mechanism, can cause apoptosis of epithelial cells and fibroblasts. This enhanced apoptosis and loss of epithelial barrier function due to DM further hinder tissue repair processes. Consequently, both cutaneous and oral complications associated with KS become more severe in diabetic patients. We report a unique case of a diabetic adolescent with KS presenting with a massive oral pyogenic granuloma and extensive periodontal destruction with a comprehensive review of the literature exploring the current understanding of oral manifestations in KS, emphasizing their under-diagnosis and potential for exacerbation by DM. This case emphasizes the need for increased awareness of oral manifestations in KS, especially in diabetic patients. Early diagnosis and a multidisciplinary approach are crucial for optimal management of cutaneous and oral complications associated with KS.